Comparison of Olson\'s Circumplex Model with Emotional Focused Couple Therapy on Psychological Well-Being in Women with Marital Dissatisfaction - Fateme Naghinasab Ardehaee; Mahmoud Jajarmi; Mohammad Mohammadipour (Golestan University of Medical Sciences, 2018)
Background: Improving the level of psychological well-being is one of the psychological concerns of the recent century. This study was conducted to compare the Olson's Circumplex Model with Emotional Focused Couple Therapy (EFCT) on psychological well-being in women with marital dissatisfaction. Methods: the participants were sixty dissatisfied married women living in Gorgan, Iran, 2017. Having including criteria, they were randomly divided into two intervention groups. The interventions were performed for both groups through 15 sessions. The Ryff's psychological well-being scale (with six dimensions) was completed before and one week after intervention by the participants. Results: Analysis of covariance showed that both circumplex model and EFCT cause an improvement in psychological well-being. However, EFCT was more effective in the dimensions of purpose in life and personal growth. There were no significant statistical differences between two intervention methods regarding other dimensions of Psychological Well-Being. Conclusion: It is recommended to use these therapeutic approaches for couple and family therapy, preferably EFCT, to improve psychological well-being.